Current Research Problems in Administrative Studies in Poland and Germany - Kusiak-Winter, Renata (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
This publication is the result of a Polish-German scientific conference entitled “Current research problems in Administrative Studies in Poland and Germany”. The conference took place on October 21st and 22nd, 2016 in Wrocław and was organised as part of the Lower Silesian Meeting of Researchers in Administrative Studies.
Keywords: studia administracyjne; Polska; Niemcy